2007
DOI: 10.1038/sj.npp.1301661
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Moderately Beneficial Cognitive Effects of Low-Dose Treatment with Haloperidol or Clozapine in an Animal Model of the Attentional Impairments of Schizophrenia

Abstract: The absence of effective cognition enhancers for the treatment of patients with schizophrenia limits the validation of animal models and behavioral tests used for drug finding and characterization. However, low doses of haloperidol and clozapine were documented to produce moderately beneficial effects in patients. Therefore, this experiment was designed to determine the attentional effects of such treatments in a repeated-amphetamine (AMPH) animal model. Animals were trained in an operant-sustained attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 96 publications
(116 reference statements)
4
25
0
Order By: Relevance
“…Ketamine has since been used to induce a model of psychosis in normal volunteers (Abel et al, 2003; Krystal et al, 1994; Malhotra et al, 1996; Oranje et al, 2002), and to exacerbate symptoms in patients with schizophrenia (Malhotra et al, 1997a; Malhotra et al, 1997b). While the effects of psychotomimetics described above occur following acute treatment, subchronic or sensitizing regimens of drug treatment are also used to assess behavior after a washout period while drug is not on board, avoiding putative drug by drug interaction confounds (Jentsch et al, 1998; Jentsch and Roth, 1999; Martinez and Sarter, 2008; Neill et al, 2010; Young et al, 2009). Acute, subchronic, chronic, and sensitizing regimens of psychotomimetic administration will be covered below.…”
Section: Pharmacological Mouse Models Of Cognitive Dysfunction In mentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine has since been used to induce a model of psychosis in normal volunteers (Abel et al, 2003; Krystal et al, 1994; Malhotra et al, 1996; Oranje et al, 2002), and to exacerbate symptoms in patients with schizophrenia (Malhotra et al, 1997a; Malhotra et al, 1997b). While the effects of psychotomimetics described above occur following acute treatment, subchronic or sensitizing regimens of drug treatment are also used to assess behavior after a washout period while drug is not on board, avoiding putative drug by drug interaction confounds (Jentsch et al, 1998; Jentsch and Roth, 1999; Martinez and Sarter, 2008; Neill et al, 2010; Young et al, 2009). Acute, subchronic, chronic, and sensitizing regimens of psychotomimetic administration will be covered below.…”
Section: Pharmacological Mouse Models Of Cognitive Dysfunction In mentioning
confidence: 99%
“…Such low effect sizes may have contributed to the lack of FDA approval for these antipsychotics being indicated as procognitive. While basic science studies in animal models related to schizophrenia have assessed the effects of FGA or SGA, rarely have the authors discussed the relevance of the low to moderate effects of these drugs in patients (Martinez and Sarter, 2008). This approach becomes a problem when the animal models show full reversals of cognitive disruptions with antipsychotics – drugs that show minimal improvement in cognitive symptoms in patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the typical antipsychotic drug haloperidol and the atypical antipsychotic drugs clozapine and risperidone have been reported to decrease percent hits (Martinez and Sarter, 2008; Rezvani and Levin, 2004; Rezvani et al 2008). However, clozapine has been shown to reduce signal detection deficits produced by repeated-amphetamine exposure or acute MK-801 administration (Martinez and Sarter, 2008; Rezvani et al 2008). Occasional differences between the present and previous studies were observed between antipsychotic drugs for percent correct rejections.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of PD149163 to improve attention in this task, and in fact disrupt attention at the highest dose tested, suggests that PD149163 may have limited or deleterious effects on attention in schizophrenia. However, to better evaluate its treatment potential for cognitive impairment in schizophrenia, studies using deficit models that better approximate the neurocognitive deficits found in schizophrenia, including attention deficits induced by NMDA receptor antagonism (Rezvani et al 2008), caused by repeated administration of amphetamine (Kondrad and Burk, 2004; Martinez and Sarter, 2008), or occurring in rats with innate cognitive deficits (e.g., Feifel et al 2007; Feifel et al 2011), are needed to better evaluate the validity of neurotensin NTS 1 receptor agonism for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, studies employing the repeated-AMPH model of schizophrenia reported alterations in task performance and changes in neurotransmitter release that become apparent following an AMPH challenge Martinez and Sarter 2008). Therefore, a theme that seems constant across different animal models of neuropsychiatric disease is that the full spectrum of neurobiological alterations becomes most apparent in the context of neural circuitry that has been engaged, be it by task performance or a pharmacological challenge.…”
Section: Dysregulation Of Nacc Da Release In Mam Animalsmentioning
confidence: 95%